The Role of Social Media in Shaping Young Mothers’ Perceptions of Basic Immunization - Michael Wanggai; Grasella Dey; Olivia Dalika (International Journal on Health and Medical Sciences, 2025)
Basic immunization is a crucial public health intervention for preventing infectious diseases and reducing infant and child morbidity and mortality. However, immunization coverage among children of young mothers remains suboptimal in some settings, partly due to varying perceptions and beliefs influenced by information sources. This study aimed to analyze the role of social media in shaping young mothers’ perceptions of basic immunization. A quantitative cross-sectional survey design was employed involving young mothers with infants and toddlers. Participants were selected using purposive sampling based on predefined inclusion criteria. Data were collected through a structured questionnaire measuring social media exposure (frequency of use, platform type, and content credibility) and perceptions of basic immunization, including knowledge, attitudes, beliefs, and trust. Descriptive statistics and inferential analyses, including correlation and regression tests, were conducted using statistical software to examine relationships between variables. The results showed that most respondents were active daily users of social media, with Instagram and WhatsApp being the most frequently accessed platforms. The majority of young mothers demonstrated positive perceptions of basic immunization; however, a notable proportion exhibited neutral or negative perceptions linked to exposure to unverified or misleading content. Statistical analysis revealed a significant association between social media exposure and immunization perception, particularly the role of content credibility. In conclusion, social media significantly influences young mothers’ perceptions of basic immunization. Strengthening digital health literacy and engaging healthcare workers in digital communication are essential to maximize the benefits of social media for public health and reduce the impact of misinformation.